As representações sociais dos estudantes acerca do bullying no contexto escolar - Araújo, Luciene da Costa (2011)
The violence has been taking increasingly frightening proportions in our society, thus occupying a large space in current discussions. On the premise that violence is a social construction that takes place among a set of relationships and interactions among individuals, highlights the importance of the meanings attributed to the bullying by the social actors that are part of the school routine. Thus, this study aimed to understand the social representations of students about bullying, from the following types of involvement: aggressor, victim, victim-aggressor and uninvolved. This is a field research, qualitative and quantitative, developed in public elementary schools in the city of João Pessoa - PB. This study was conducted in two stages: At first, we used a sample of 346 female students and male, with ages ranging between 10 and 17 years old (M = 13.5, SD = 1.65) and the sample type of non-probability accidental. During data collection we used the free-association test, a sociodemographic questionnaire and school experiences, and the Scale of Aggression and Peer Victimization - EVAP; the second step, were the application of SCAN-Bullying with a subsample of 32 students. In the analysis of the demographics data and the Scale of Aggression and Peer Victimization (EVAP) were used descriptive and inferential statistics (chi-square). By analyzing the EVAP found that 39% of students were not involved in bullying, 27% were identified as aggressors, 23% behaved as aggressors and victims, 11% were identified as victims. The data obtained through the free-association test were processed by software Tri-Deux-Mots, revealing that bullying was represented in a manner similar to its theoretical definition, classified as direct attacks (punches and kicks), indirect (through threats) and as verbal aggression (insults, nicknames), also associated with racism and prejudice. To effect the analysis of SCAN-Bullying was used the ALCESTE software. By this analysis, showed that students identified as victims accounted bullying from their victimization experiences, highlighting how the support was perceived on these situations. The aggressor have attributed positive feelings to the role of aggressor, associate the idea of power and popularity, justifying victimization to the victim's personal characteristics or in terms of socio-cultural stereotypes. Victims-aggressors accounted bullying as direct and indirect physical aggression, manifesting behaviors of hitting back the aggression. Students who were not involved in bullying revealed a concern with coping strategies. These results were discussed within the literature, indicating convergence with some findings. We also sought to raise the potential limitations of the study.